Answers

2014-06-15T11:18:46+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
You can use factoring, completing the square and the formula
0
x2 + 4x + 4 = -1 + 4
(x + 2)2 = 3
Step 4 Take the square root on both sides of the equation:
x + 2 = ±√3 = ±1.73 (to 2 decimals)
Step 5 Subtract 2 from both
(not my examples)
tnx 4 ur best answer.nowXCzvmVo
now i know
yeah
2014-06-15T11:23:08+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
You can factor it or complete its square

Example:

By factoring,

x²-4=0
(x+2)(x-2)
x=-2 x=2

By completing its square,

x²-4=0
√x² and √4
x= ±2

0